THE CONTRIBUTION OF PURSE SEINE FISHERY HOME-BASED IN THE COASTAL FISHING PORT OF TUMUMPA ON GROSS REGIONAL DOMESTIC PRODUCT (GRDP) OF MANADO - Sjamsuddin, Gusari; Sitanggang, Effendi P; Budiman, Johnny (Graduate Program of Sam Ratulangi University, 2013)
The coastal fishing port of Tumumpa has a primary supply of marine fishes caught by purseseiners to fulfill the Manadonian needs. This descriptive study using literature and field research is to determine the contribution of purseseine fishery to the gross regional domestic product (GRDP) of Manado. The results showed that the sub-sector of fishery has a LQ (location quotient) < 1 (average 0.30). It means, the sub-sector of fishery in Manado is not an important sector in Manado. To fulfill the Manadonian needs, import of fish is expected to be necessary. The purseseine fishery has a high contribution to the GRDP of Manado, from 1.58% in 2003 to 82.5% in 2012 (annual average of 30.5%) with average growth of 71.5% per year, based on market price. The revenue of ship?s crews depends on each person's responsibility on the ship. Financial analysis concluded that purseseine fishery is economically feasible with R/C ratio varying from 1.09 to 1.22 (average 1.16). The operational costs must be the owners? responsibility, which reduces revenue disparity between owners and crews. Considering the lack of fish supply and the fact that marine fishes of North Sulawesi seawaters still have high potential, it is recommended to add some new purseseiners. Pelabuhan Perikanan Pantai (PPP) Tumumpa Manado menjadi pemasok utama ikan yang tertangkap oleh kapal pukat cincin untuk masyarakat Kota Manado. Penelitian deskriptif yang menggunakan library research dan field research ini bertujuan mengetahui sampai sejauh mana kontribusi perikanan pukat cincin ini terhadap produk domestik regional bruto (PDRB) Kota Manado. Dari analisis data diperoleh bahwa subsektor perikanan memiliki nilai LQ < 1 (rerata 0,30) yang berarti subsektor perikanan di Kota Manado bukanlah merupakan sektor basis bagi perekonomian Kota Manado. Dengan demikian, untuk memenuhi kebutuhan masyarakat dari subsektor perikanan tersebut perlu dilakukan impor. Perikanan pukat cincin ini berkontribusi tajam dari tahun ke tahun terhadap PDRB Kota Manado, dari 1,6% tahun 2003 menjadi 82,5% tahun 2012 (rerata 30,5% per tahun), dengan kenaikan rerata 71,5% per tahun (ADHB). Pendapatan kru kapal dibedakan sesuai tugas dan tanggungjawab di kapal. Usaha perikanan pukat cincin ini layak secara finansial, dengan nilai R/C rasio 1,09 - 1,22 (rerata 1,16). Biaya operasional seyogianya menjadi tanggungan pemilik untuk mengurangi disparitas pendapatan antara pemilik dan kru kapal. Mengingat kurangnya pasokan ikan dan masih cukup tersedianya potensi lestari sumberdaya perikanan laut di perairan Sulawesi Utara, penambahan kapal pukat cincin seyogianya mutlak dilakukan.